2017
DOI: 10.1002/lary.26566
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human papillomavirus on the clinical presentation of oropharyngeal carcinoma in the United States

Abstract: 4. Laryngoscope, 127:2270-2278, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 33 publications
1
34
1
9
Order By: Relevance
“…HPV‐positive patients also have significantly improved prognosis compared with HPV‐negative patients, with higher response rates to chemoradiation treatment, higher control rates with surgery and adjuvant treatment, and better overall survival both at diagnosis and after disease progression, relative to HPV‐negative OPSCC patients . Recent studies have also shown that the extent of nodal disease differs for HPV‐positive and HPV‐negative OPSCC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV‐positive patients also have significantly improved prognosis compared with HPV‐negative patients, with higher response rates to chemoradiation treatment, higher control rates with surgery and adjuvant treatment, and better overall survival both at diagnosis and after disease progression, relative to HPV‐negative OPSCC patients . Recent studies have also shown that the extent of nodal disease differs for HPV‐positive and HPV‐negative OPSCC …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Recent studies have also shown that the extent of nodal disease differs for HPV-positive and HPVnegative OPSCC. 22 With the recognition that HPV-positive and HPVnegative OPSCC have different etiologies, clinical-demographic characteristics, and prognostic profiles, the two are now considered distinct entities despite arising from the same anatomic site. However, the clinical factors that influence overall survival for these separate diseases remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing smoking rates in the past three decades, however, have not curbed the increasing incidence of OPSCC . This phenomenon has clarified that high‐risk serotypes of human papillomavirus (HPV) are an established cause and significant risk factors for OPSCC …”
Section: Introductionmentioning
confidence: 99%
“…By a definition based on the earlier staging systems, patients with moderately advanced lymph node disease (N2) would be considered as having stage IV. [21][22][23] An important finding from the current study is that patients with oropharyngeal cancer are at risk of developing distant disease. It has long been known in the management of HNC that advanced lymph node disease is a harbinger of poor prognosis and predicts distant failure.…”
Section: Discussionmentioning
confidence: 76%
“…Approximately 75% of cases of oropharyngeal cancer are associated with HPV, and these tumors often present with small primary tumors and larger cystic regional lymph node metastases as the first notable symptom, rather than the metastasis often observed in patients with HPV‐negative HNC. By a definition based on the earlier staging systems, patients with moderately advanced lymph node disease (N2) would be considered as having stage IV . An important finding from the current study is that patients with oropharyngeal cancer are at risk of developing distant disease.…”
Section: Discussionmentioning
confidence: 92%